ARTI SIMBOLIS PAHATAN NAGA DI BAWAH CERAT YONI DARI SINGASARI - Rita Istari (BRIN, 2003)
Yoni, which is made of andesite stone, also has different meanings. The stones for yoni from the production process can be classified into four types, namely: very young stones (bala), young stones (Yuya), middle stones (Madnya) and old stones (wreddha). In addition, it can also be classified into: male stones, female stones and neutral stones. Stone color also has its own meaning, namely: white symbolizes equality, red symbolizes glory, yellow symbolizes prosperity and black symbolizes fertility. Stone for yoni is usually a type of female stone. This fact is in accordance with the opinion that says that yoni is a female element. Most of the yoni is made of black andesite stones, this is in line with the meaning of yoni as a female symbol associated with fertility.